2014
DOI: 10.1016/j.celrep.2014.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Selective Protection of an ARF1-GTP Signaling Axis by a Bacterial Scaffold Induces Bidirectional Trafficking Arrest

Abstract: SUMMARY Bidirectional vesicular transport between the endoplasmic reticulum (ER) and Golgi is mediated largely by ARF and Rab GTPases, which orchestrate vesicle fission and fusion, respectively. How their activities are coordinated in order to define the successive steps of the secretory pathway and preserve traffic directionality is not well understood in part due to the scarcity of molecular tools that simultaneously target ARF and Rab signaling. Here, we take advantage of the unique scaffolding properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…Consistent with previous in vitro data [25], EspG was preferentially co-immunoprecipitated with GTP-bound rather than GDP-bound ARF6 (Fig. 2a).…”
Section: Espg Preferentially Interacts With Active Arf6 To Localize Asupporting
confidence: 92%
“…Consistent with previous in vitro data [25], EspG was preferentially co-immunoprecipitated with GTP-bound rather than GDP-bound ARF6 (Fig. 2a).…”
Section: Espg Preferentially Interacts With Active Arf6 To Localize Asupporting
confidence: 92%
“…We showed previously that Nocodazole prevents membrane trafficking beyond ERGIC in a manner analogous to Rab1 inhibition by the VirA homolog EspG (Selyunin et al, 2014). Brefeldin A (BFA) potently inhibits ARF1 GTPase and can therefore be considered ‘IpaJ-like’.…”
Section: Resultsmentioning
confidence: 93%
“…Microinjection experiments was done as described in (Selyunin et al, 2014). Briefly, microinjections of IpaJΔ50 and VirAΔ26 were performed using a semiautomatic InjectMan NI2 micromanipulator (Eppendorf).…”
Section: Methodsmentioning
confidence: 99%
“…In the same study, EPEC EspG was shown to reduce hGH secretion and IL-8 release. The phenotypes of both VirA and EspG were attributed specifically to Rab1 inactivation and the resultant decrease in ER-Golgi transport (Dong et al ., 2012), and a model of EspG activity has been proposed where EspG interacts with ARF1 at the cis -Golgi membrane and deactivates the local Rab1 population resulting in bidirectional ER-Golgi trafficking arrest (Selyunin et al ., 2014). …”
Section: Introductionmentioning
confidence: 99%